Em cena: a constituição do professor do atendimento educacional especializado - Dorneles, Marciele Vieira (2013)
This study aims to problematize how the discursive productions of care Specialized Education (ESA) have produced modes of being Special Education teacher in inclusive education and what are the effects of these discourses in their teaching practices. For this, we use a range of analysis tools extracted from the writings of authors who share their thinking and research using poststructuralist thoughts, like as: the notion of modes of subjectivity, for thinking about the discourses and practices that are in a network of power and knowledge defining, a certain way, teachers of Special Education and regulating their conduct, as well as the notion of experience and narratives of self, de Jorge Larrosa. The research involved the collaboration of six teachers of Special Education working in ESA, which made reports on their experiences in educational practice and how they constituted themselves as professionals in the currently prevailing neoliberal rationality. Thus, it was observed that the Special Education teachers are experiencing conflicts with regard to working in Resource Room Multifunctional and an uncertainty of their role in school. Given the problematization presented, noted that the Special Education teacher are feeling a "emptying professional" , that is , at the same time that you are given numerous assignments - perhaps more focused on the use of technologies and management - leave behind the pedagogical actions.